Optimization of Soft X-Ray Fresnel Zone Plate Fabrication Through Joint Electron Beam Lithography and Cryo-Etching Techniques - Maha Labani; Vito Clericò; Enrique Diez; Giancarlo Gatti; Mario Amado; Ana Pérez-Rodríguez (Nanomaterials)
The ability to manufacture complex 3D structures with nanometer-scale resolution, such as Fresnel Zone Plates (FZPs), is crucial to achieve state-of-the-art control in X-ray sources for use in a diverse range of cutting-edge applications. This study demonstrates a novel approach combining Electron Beam Lithography (EBL) and cryoetching to produce silicon-based FZP prototypes as a test bench to assess the strong points and limitations of this fabrication method. Through this method, we obtained FZPs with 100 zones, a diameter of 20 µm, and an outermost zone width of 50 nm, resulting in a high aspect ratio that is suitable for use across a range of photon energies. The process incorporates a chromium mask in the EBL stage, enhancing microstructure precision and mitigating pattern collapse challenges. This minimized issues of under- and over-etching, producing well-defined patterns with a nanometer-scale resolution and low roughness. The refined process thus holds promise for achieving improved optical resolution and efficiency in FZPs, making it viable for the fabrication of high-performance, nanometer-scale devices.